Law clinics and advocacy within the university community: risks and benefits (2017)
The inception of the legal aid scheme in the Nigerian legal system brought about hope for the indigent and with it an increased rate of indigent dependents relying on the scheme to access justice. This article discusses the advent of legal clinics in Nigeria and its relevance to a university community; in particular, the writers look into the rationale for establishing a specialized Woman’s Law Clinic and discuss the risks and benefits associated with advocacy and practicing as a University Law Clinic. In concluding, a risk–benefit assessment was examined using the unstructured questionnaire method of finding the stakeholders’ views/perspectives on having a clinic within the university community.